Measuring the operating efficiency of internet channels with DEA. (5th April 2010) - Tu, Hung-Jen; Yen, Wan-Chu; Hou, Jia-Jeng
The emergence of the internet has forced a wealth of firms to explore a new form of channels of distribution, i.e., internet channels. Managing the impact of introducing an internet channel into an existing distribution system is probably one of the greatest challenges today. This research employs data envelopment analysis (DEA) approach to measure the operating efficiency of internet channels. To improve the effectiveness of the DEA in contributing to group consensus and decision-making, the integration of DEA with Delphi method is proposed. Empirical data are collected from the financial service sector in Taiwan. The findings demonstrate the existence of large inefficiencies. In order to improve the logisitics economics of the inefficient firms, this study further provides guidelines for managers that will eventually benefit policy-making in resource allocation and in strengthening its management.